Korovkin second theorem via B-statistical A-summability - Mursaleen, Mohammad; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
Korovkin type approximation theorems are useful tools to check whether a given sequence (Ln) n ≥ 1 of positive linear operators on C [ 0,1 ] of all continuous functions on the real interval [ 0,1 ] is an approximation process. That is, these theorems exhibit a variety of test functions which assure that the approximation property holds on the whole space if it holds for them. Such a property was discovered by Korovkin in 1953 for the functions 1, x, and x 2 in the space C [ 0,1 ] as well as for the functions 1, cos, and sin in the space of all continuous 2 π -periodic functions on the real line. In this paper, we use the notion of B -statistical A -summability to prove the Korovkin second approximation theorem. We also study the rate of B -statistical A -summability of a sequence of positive linear operators defined from C 2 π (ℝ) into C 2 π (ℝ).